Peran Rekrutmen Online Koperasi Putra Daerah Transindo dalam Perekrutan Tenaga Kerja untuk PT. Grab Kota Makassar - Nfn Sudirman (Program of Communication Sciences, Faculty of Social and Political Sciences, UIM, 2019)
This study aims to determine the role of online media in the recruitment of workers in PT. Grab Makassar City and to determine the supporting factors and inhibiting factors. This research is a descriptive qualitative research, which is a method used to describe or analyze a research result but not used to make broader conclusions the steps are in the form of observation, interviews and documentation in the field as for the location of the research in the Putra Putra Putra Transido Cooperative as a partner of PT. Makassar City Grab. The results showed that the role of online media in the recruitment of workers in the company can be said to be very instrumental in terms of profits for the company or potential drivers or employees as for the supporting factors that do not require a long time in various recruitment processes from the company and easier to get information in recruitment while the inhibiting factors are network instability, incomplete registration file and the use of a cellphone camera that is not good.